A Historical Background of Some Basic ICT Tools Used in Counterfeit Drug Control - Amusa, Morufu; Oluwade, Bamidele (2020)
Counterfeit drugs impose risk to human life and properties. Many organizations globally are involved in campaigning for counterfeit drugs control. Almost all these efforts are focused on control at various stages of production and supply chain, while less or rare efforts are invested at terminal intervention by the end users. In this paper, a historical background of some of the existing applications of ICT to counterfeit drug control is presented. These basically revolve round the Global System of Mobile Communication (GSM), mainly voice and text; Internet technology is faintly mentioned. The paper is expected to provide background resource for an efficient and effective information system capable of preventing and/or minimizing the risks resulting from counterfeit drugs. The ultimate goal is to develop products which will assist counterfeit drug control agencies and health information related agencies.